Análise crítica do discurso de decisões judiciais: um estudo do uso da "proporcionalidade" e da "razoabilidade" como ferramentas de decisão - Campello, Juliana Endriss Carneiro (2014)
This research investigates the construction of legal discourse in cases decided using the concepts of "proportionality and reasonableness as decision tools. The methodology is based on the Critical Discourse Analysis (CDA), that conceives the use of language in a three-dimensional perspective, but also, the analysis of text within a discursive practice and this immersed in a social practice. This agenda of work, applied to data in legal proceedings, seeks to dislodge the idea that language is merely an instrument for the realization of Law. The approach is based on the idea that one should overcome the positivist view of ready and finished standard text, and that the normative meaning is constructed by the judge through ideologically driven textual interpretation. This study is justified by the fact that the use of "proportionality and "reasonableness" as instruments of legal legitimacy of judicial decisions has been causing drastic fluctuation of normative senses and therefore differing judgments in similar cases, masking ideological positions of the judge on social issues that permeate the judicialized conflicts.